2015
DOI: 10.1108/ejim-08-2013-0081
|View full text |Cite
|
Sign up to set email alerts
|

User participation and stakeholder involvement in health care innovation – does it matter?

Abstract: Purpose – The purpose of this paper is to discuss how and to what extent users can become involved in the process of selecting and implementing telecare and telehealth technologies in local health care services. Design/methodology/approach – The discussion is based on data from a project in one local authority in Norway. About 100 persons have participated in focus group interviews where issues regarding new telecare and telehealth techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 16 publications
0
38
0
Order By: Relevance
“…As for the workshop example, although fast prototyping tools like littleBits® were used, it still takes some time and effort to produce working physical prototypes. By using both approaches we were able to get the benefits of both a wide range of visualized ideas, and a few more concrete examples -something that can be particularly important when also involving users who are unfamiliar with the technology and may have cognitive difficulties [4,5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the workshop example, although fast prototyping tools like littleBits® were used, it still takes some time and effort to produce working physical prototypes. By using both approaches we were able to get the benefits of both a wide range of visualized ideas, and a few more concrete examples -something that can be particularly important when also involving users who are unfamiliar with the technology and may have cognitive difficulties [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…Björkquist, Ramsdal et al [4] found that it can be difficult to involve older senior users in focus groups due to lack of information about different services. There is also the challenge of adapting activities to suit the prospective users.…”
Section: Co-design With Stroke Survivorsmentioning
confidence: 99%
“…The above items can be summarized under the term user practice. Apparently, thorough knowledge of this user practice is of great importance [35].…”
Section: General Satisfactionmentioning
confidence: 99%
“…Current work on co-design has largely focused fully ablebodied people, and it can be difficult to involve persons who are disabled and/or elderly in this process. Björkquist, Ramsdal et al [11] found that it can be difficult to involve older senior users in focus groups due to lack of information about different services. There is also the challenge of adapting activities to suit the prospective users.…”
Section: Design Processmentioning
confidence: 99%